Prospects for 4-laser white-light sources. Issue 3 (6th February 2019) - Soltic, Snjezana; Chalmers, Andrew N.
ABSTRACT: This paper describes a series of simulation experiments designed to demonstrate the feasibility of using solid-state lasers in white-light mixtures. The mixed-laser sources are evaluated in terms of the luminous efficacy of the radiation (LER) as well as different measures of colour performance. The latter include the CIE colour rendering index ( Ra ) and the IES colour fidelity index ( Rf ) as well as a selection of additional parameters in the two systems. Optimization of the mixtures is achieved by the use of purpose-designed differential evolution algorithms. The best results to date (with four real laser wavelengths) are Rf of 84 with LER 364 lm/W, which indicate the feasibility of the mixed-laser approach to provide highly efficient, energy-saving light sources. These prospects will be further enhanced by potential future developments in semiconductor lasers, with the possibility of producing Rf of 86 with LER of 380 lm/W.